VD_FINDINFO Jug / 2011 / 59 vom 11. April 2011 - VD Tribunal cantonal (2011)
RÉVISIONDÉCISION, ADMISSION DE LA DEMANDE, NOUVEAU MOYEN DE FAIT, LÉSÉ, MOTIF DE RÉVISION | 115 LEtr, 410 al. 1 let. a CPP (CH), 413 al. 2 let. a CPP (CH), 414 al. 1 CPP (CH)